A photobioreactor system for precision cultivation of photoautotrophic microorganisms and for high-content analysis of suspension dynamics - Nedbal, Ladislav; Trtílek, Martin; Cervený, Jan; Komárek, Ondrej; Pakrasi, Himadri B (Biotechnology and bioengineering, 2008)
Small-scale photobioreactors for cultivation of photoautotrophic microbes are required for precise characterization of the growth parameters of wild-type and engineered strains of these organisms, for their screening, and for optimization of culture conditions. Here, we describe the design and use of a flat-cuvette photobioreactor that allows accurate control of culture irradiance, temperature, pH, and gas composition combined with real-time monitoring by a built-in fluorometer and densitometer. The high-power LED light source generates precise irradiance levels that are programmed by user-designed protocols. The irradiance, temperature, and gas composition may be static or dynamically modulated, while optical density and pH may be stabilized in turbidostat and pH-stat modes, respectively. We demonstrate that the instrument is able to detect minute variations of growth caused, for example, by sudden dilution or by circadian rhythms. The sensitivity of the instrument is sufficient to monitor suspension optical density as low as 10(-2). This newly designed photobioreactor can significantly contribute to the study and use of photoautotrophic microbes in systems biology and biotechnology.
Keywords: Cell Culture Techniques; buněčné kultury; Cyanobacteria; Colony Count, Microbial; fotobiologie; bioreaktory; monitorování fyziologických funkcí; počet mikrobiálních kolonií; design vybavení; Bioreactors; sinice; Equipment Failure Analysis; Equipment Design; Monitoring, Physiologic; analýza selhání vybavení; Photobiology